Respuestas

  • Usuario de Brainly
2013-12-07T17:55:28+01:00
Tn = ar^(n-1)

a1 = a
a2=  ar
a3= ar²
a4=ar³

=> a2 = ar  = 3/2
       ⇔ a = 3/2r ..........(1)

=> a4 = ar³ = 6
         ⇔ a = 6/r³...........(2)

De (1) y (2) :

3/2r = 6/r³  ,  x ≠ 0
3r³ = 12r
r² =4
r = + 2


Si: r = -2

a = 3/2(-2)
a = -3/4

⇒ tn = (-3/4) (-2) ^(n-1) =

Producto de los 3 primeros terminos = a1.a2.a3 = a³(r)³ = (-3/4)³ (-2)³ = 27/8


Si: r = + 2

a = 3/2(+2)
a = 3/4

⇒ tn = (3/4) (2) ^(n-1)

Producto de los 3 primeros terminos = a1.a2.a3 = a³(r)³ = (3/4)³ (2)³ = 27/8